Patients With Severe Alcohol-Related Cognitive Impairment Improve in Flexibility When Abstinence Is Maintained: A Comparative Study With Alzheimer’s Disease - Clergue-Duval, Virgile; Barré, Thomas; Cognat, Emmanuel; Brichet, Anne-Laure; Géraud, Claire; Azuar, Julien; Michaud, Philippe; Lecallier, Dorothée; Arfaoui-Geffroy, Sonia; Hispard, Eric; Paquet, Claire; Bellivier, Frank; et al. (Frontiers in Psychology, 2022)
The disease progression of severe alcohol-related cognitive impairment (ARCI) is debated. The aim of this study was to compare the cognitive change of patients with severe ARCI in inpatient setting to that of patients with Alzheimer’s disease (AD). Fifteen consecutive patients with severe ARCI were recruited between 2013 and 2015. They received inpatient detoxification, neurological assessment, and inpatient cognitive rehabilitation in specialized facilities. Twelve patients, with documented AD matched on sex and initial cognitive impairment severity, were selected. All have benefited from two neuropsychological assessments. The neurocognitive change was tested in both groups with pair-wised Wilcoxon tests. ARCI and AD patients’ time course was compared with Mann–Whitney–Wilcoxon test. In ARCI group, first assessment occurred at 2.9 (± 2.2) months of abstinence and follow-up 6.5 (± 2.9) months later, the mean age was 56.5 (± 7.4) years, and 12 were men. In AD group, follow-up occurred at 12.8 (± 2.9) months (p < 10–3), the mean age was 72.3 (± 8.4) years (p < 10–3), and 10 were men. ARCI patients significantly improved on one executive function test (TMT-B; p < 0.05), while AD patients have worsened memory subtests on Free-and-Cued-Selective-Reminding Test (p < 0.05). These tests showed a statistically different change between severe ARCI and AD group (p < 0.05). Severe ARCI patients have improved in executive functioning, discernible on the TMT-B test, in specific care setting, including abstinence maintenance and rehabilitation. The disease progression was different from that observed in AD patients.